UPTAKE OF NICKEL(II) USING DIMETHYLGLIOXYME CHELATE ANION EXCHANGE RESIN - Nugraheni, Nugraheni VD; Gunawan, Gunawan; Junaedi, Cholik Muhammad (JURNAL SAINS DAN MATEMATIKA, 2010)
ABSTRACT---Uptake  of   nickel(II)   ions  from  solution  are studied  using  strong  base  anion   resin   ( Lewatit  M500, counter  ions  of  Cl-)  and  dimethylglyoxime   (2,3-butanedione dioxime,  H2DMG) as chelating agent. This study was conducted to determine optimum condition of chelate resin preparation for uptake of nickel(II)  ions  from  solution. The research used batch and column techniques. Batch technique was used to determine the best contact time at  chelate  resin preparation, capacity  of chelate resin ( mg Ni2+/ g), effect of pH stripping  (pH 1- 5)  and  pH  of  nickel(II)   solution  (pH 4 - 10)   to   capacity   of  chelate resin  as  well  as  effect of  pH  backwash  (pH 1- 5)  to  percentage  of  nickel(II)  ions  recovery. Column  technique  was  used  for  uptake of  nickel(II) ions  from  waste   water of  industrial  of  metal  veneering. Column flow rate was kept constant at 2 mL/ minute. Nickel(II) ions which were not removed by chelate resin was quantitatively  analyzed with atomic absorption spectrophotometer at wavelength  of 232,00 nm. Result  of  the  research   revealed   the   best   contact   time  at chelate  resin preparation   was  120 - 240   minutes   for   variation  of  contact  time   from  0 to 240 minutes to each 25 gram strong base anion resin. Capacity of chelate resin was obtained about 0,209 to 0,214 mg Ni2+/ g chelate resin. Capacity of  chelate   resin  decreased  progressively  after  process of   stripping  that was  0,217 - 0 mg Ni2+/ g  from pH of 5 to 1. The best range pH of nickel(II) solution was obtained at pH of 6 to  7 with capacity of chelate resin from 0,239 to 0,241 mg Ni2+/ g and selected at pH 6. Percentage recovery of nickel(II) ions increased 21,966 to 75,314% from pH backwash of 5 to 1. With column technique, chelate resin capacity was obtained 0,208 mg Ni2+/ g and breakthrough point was reached when flow times reached in 60 to 80 minutes.Permalink : http://ejournal.undip.ac.id/index.php/sm/article/view/2854